Comprehensive Analysis of Financial Performance at PT Jakarta International Hotels & Development TBK Periode 2021-2023 - Sanjaya, I Ketut Raditya; Arwana, I Putu; Tuwi, I Wayan (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research analyzes the financial performance of PT Jakarta International Hotels & Development Tbk from 2021 to 2023 using financial ratios to comprehensively evaluate financial conditions. Qualitative methodology and descriptive techniques are used. The research results show that the liquidity ratio has increased, reflecting the company's ability to manage assets and liabilities well. The solvency ratio shows a decline, indicating a solid and solvable financial condition. Activity ratios indicate high operational efficiency with fast turnaround. Profitability ratios show significant recovery after losses in 2021 due to the Covid-19 pandemic. This research provides insight into the company's financial condition and emphasizes the importance of sustainable financial monitoring and strategic management for long-term growth in the hotel industry.